Systematic review meta-analysis protocol preparation and registration – A narrative review - Indubala Maurya; Rakesh Garg (Indian Journal of Anaesthesia, 2025)
Systematic reviews and meta-analyses (SRMAs) help in decision making, especially on conflicting publication findings and quality. SRMA identifies the source of heterogeneity, reduces subjectivity and identifies and fills gaps in existing knowledge. However, conducting an SRMA requires a well-written protocol, which acts as a clear roadmap for the researcher and defines objectives, methods and expected outcomes. Predefined research questions and methods minimise bias, thus increasing the reliability of the results. The protocol ensures that the study team stays consistent in data collection, synthesis and interpretation. The SRMA protocol includes rationale, hypothesis, aims and methodology. A detailed protocol improves the overall quality of the research. All SRMA protocols must be registered and made available publicly. Protocol registration ensures transparency in the research process, which avoids the wastage of resources and prevents duplication. A well-planned protocol facilitates faster peer review and enhances the chances for publication. This narrative review primarily focuses on SRMA protocol preparation and its registration.